Co-expression with the Type 3 Secretion Chaperone CesT from Enterohemorrhagic E. coli Increases Accumulation of Recombinant Tir in Plant Chloroplasts - MacDonald, Jacqueline; Miletic, Sean; Gaildry, Typhanie; Chin-Fatt, Adam; Menassa, Rima (Frontiers in Plant Science, 2017)
Type 3 secretion systems (T3SSs) are utilized by pathogenic Escherichia coli to infect their hosts and many proteins from these systems are affected by chaperones specific to T3SS-containing bacteria. Towards developing a recombinant vaccine against enterohaemorrhagic E. coli (EHEC), we expressed recombinant T3SS and related proteins from predominant EHEC serotypes in Nicotiana chloroplasts. Nicotiana benthamiana were transiently transformed to express chloroplast-targeted Tir, NleA, and EspD from the EHEC serotype O157:H7; a fusion of EspA proteins (EspA-2) from serotypes O157:H7 and O26:H11; and a fusion of epitopes of Tir (Tir-ep) from serotypes O157:H7, O26:H11, O45:H2, and O111:H8. C-terminal GFP reporter fusion constructs were also developed and transiently expressed to confirm subcellular localization and quantify relative expression levels in situ. Recombinant proteins were co-expressed with chaperones specific to each T3SS protein with the goal of increasing their accumulation in the chloroplast. We found that co-expression with the chloroplast-targeted chaperone CesT significantly increases accumulation of recombinant Tir when the latter is either transiently expressed in the nucleus and targeted to the chloroplast of N. benthamiana or stably expressed in transplastomic Nicotiana tabacum. CesT also helped maintain higher levels of Tir:GFP fusion protein over time both in vivo and ex vivo, indicating that the favourable effect of CesT on accumulation of Tir is not specific to a single time point or to fresh material. By contrast, T3SS chaperones CesT, CesAB, CesD, and CesD2 did not increase accumulation of NleA:GFP, EspA-2:GFP, or EspD:GFP, which suggests dissimilar functioning of these chaperone-substrate combinations. CesT did not increase accumulation of Tir-ep:GFP, which may be due to the absence of the CesT binding domain from this fusion protein. The fusion to GFP improved accumulation of Tir-ep relative to the unfused protein, but not for the other recombinant proteins. These results emphasize the importance of native chaperones and stabilizing fusions as potential tools for the production of higher levels of recombinant proteins in plants; and may have implications for understanding interactions between T3SS chaperones and their substrates. In particular, our findings highlight the potential of T3SS chaperones to increase accumulation of recombinant T3SS proteins in heterologous systems.